2017
DOI: 10.18632/oncotarget.15482
|View full text |Cite
|
Sign up to set email alerts
|

Multi-targeting therapeutic mechanisms of the Chinese herbal medicine QHD in the treatment of non-alcoholic fatty liver disease

Abstract: Beneficial effects of the Chinese herbal medicine Qushi Huayu Decoction (QHD) were observed with non-alcoholic fatty liver disease (NAFLD) patients and animal models. The impact of QHD or its active components (geniposide and chlorogenic acid, GC) on NAFLD liver transcriptome and gut microbiota was examined with NAFLD rats. Increased expression for genes required for glutathione production and decreased expression for genes required for lipid synthesis was observed in NAFLD livers treated with QHD and GC. GC t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
52
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 54 publications
(54 citation statements)
references
References 52 publications
1
52
0
Order By: Relevance
“…Mouzaki, et al, reported a significant link between the presence of NASH and low percentages of Bacteroidetes in fecal samples, but not BMI, suggesting that intestinal flora may play an important role in the development of NAFLD [27]. An imbalanced gut flora could increase the production of endotoxins or even result in intestinal endotoxemia, which are important factors involved in secondary liver damage as well as the disease progression of NAFLD [28,29]. In return, the development of NAFLD affects the intestinal micro-ecological balance, forming a vicious circle.…”
Section: Discussionmentioning
confidence: 99%
“…Mouzaki, et al, reported a significant link between the presence of NASH and low percentages of Bacteroidetes in fecal samples, but not BMI, suggesting that intestinal flora may play an important role in the development of NAFLD [27]. An imbalanced gut flora could increase the production of endotoxins or even result in intestinal endotoxemia, which are important factors involved in secondary liver damage as well as the disease progression of NAFLD [28,29]. In return, the development of NAFLD affects the intestinal micro-ecological balance, forming a vicious circle.…”
Section: Discussionmentioning
confidence: 99%
“…In a case-control study, serum free fatty acid (FFA) profiles were significantly higher in patients with NAFLD than healthy controls; these FFA profiles were positively associated with almost all metabolic indicators, especially blood glucose, lipid and liver enzymes. 101 The study observed 14:0 and 16:1 as unique FFAs of prominent diagnostic importance for the early screening of NAFLD. Lean and overweight patients with NAFLD had similar concentrations of all FFAs, but obese patients with NAFLD presented significantly higher levels of all types of FFA.…”
Section: Insulin Resistance As a Key Element In The Development Of Namentioning
confidence: 85%
“…Recent studies showed that administration of Qushi Huayu Decoction (QHD) significantly decreased body weight, alleviated hepatic steatosis, and reduced the content of TG and free fatty acids in liver in HFD-induced NAFLD rats. It showed that the CHF-treated group harbored significantly different gut microbiota from that of model rats, and the bacterial profiles of NAFLD rats could be modulated by the CHF [163,164]. Recently, the anti-obesity property of daesiho-tang (DSHT) was also investigated.…”
Section: Gut Microbiota-targeted Therapies With Other Approachesmentioning
confidence: 99%